Dysregulated macrophage immunity in Helicobacter pylori infection: unveiling mechanistic insights and therapeutic implications - Xiang, Miao; Li, Panpan; Yue, Xiaofei; Liu, Linlin; Wang, Linjing; Sun, Nengjin; Wang, Kaile; Zhang, Yuying; Wang, Hongyan (Frontiers in Immunology, 2025)
Helicobacter pylori (H. pylori) is a microaerophilic, gram-negative spirochete that primarily colonizes the human gastric mucosa. It is strongly linked to gastritis, ulcers, and the development of malignant tumors. Macrophages, as one of the key components of the innate immune system, play a crucial role in maintaining immune homeostasis through a range of functions, including pathogen phagocytosis, antigen recognition and presentation, inflammation regulation and tumor immune surveillance. Emerging evidence suggests that H. pylori employs diverse molecular mechanisms to evade immune clearance by macrophages. This review provides a comprehensive analysis of how H. pylori infection modulates macrophage functions, including impairing pathogen recognition and phagocytosis, disrupting phagosome maturation and reducing immune clearance capacity. Furthermore, H. pylori infection skews macrophage polarization to promote chronic inflammatory damage, inhibits antigen processing and presentation to evade adaptive immune responses and induces macrophage apoptosis via activation of apoptotic signaling pathways. By unraveling the complex molecular interactions between H. pylori and macrophages, this review highlights strategies for reprogramming macrophage functions, offering innovative approaches to address the limitations of conventional antimicrobial therapies and advancing targeted therapeutic interventions for H. pylori-associated diseases.